Development of an Evidence-Based List of Noncytotoxic Vesicant Medications and Solutions. Issue 1 (January 2017) - Gorski, Lisa A.; Stranz, Marc; Cook, Lynda S.; Joseph, James M.; Kokotis, Kathy; Sabatino-Holmes, Pam; Van Gosen, Lori
Abstract : Infiltration of a vesicant medication, defined as extravasation, may result in significant patient injuries. The first step in preventing extravasation is the identification and recognition of vesicant medications and solutions. Because there is no list of noncytotoxic vesicants as established by a professional organization, the Infusion Nurses Society, as the global authority in infusion nursing, identified the need to address this gap. A task force was formed for the purpose of creating an evidence-based list of noncytotoxic vesicant medications and solutions.